Echocardiographic abnormalities in non-moderate drinking of alcohol for prolonged duration - Gautam, MP; Gautam, U Ghimire; Dwivedi, S; Rijal, S (Journal of College of Medical Sciences-Nepal, 2010)
Background: Alcohol drinking is cardio-protective; however its beneficial and harmful effects depend on the amount consumed. This work is designed to assess the impact of prolonged non-moderate drinking in left ventricular mass index and left ventricular ejection fraction and the correlation of their severity with total lifetime intake amount. Materials and methods: Fifty non-moderate drinkers (>25 g/day) for last 10 years and 50 non-drinker-volunteers were selected. Detail echocardiographic assessment was done and findings were compared and severity was correlated with lifetime amount. Results: Mean daily intake, duration and lifetime intake amount of alcohol were 64.1 g, 21.9 years and 501.9 Kg respectively. The mean ejection fraction and left ventricular mass index were 47.2% and 105.3 g/m2. There was significant difference when compared with controls. Eighty-two percent drinking subjects had abnormal echo, most common were regurgitations (52%), diastolic dysfunction (46%), raised ventricular mass (44%), systolic dysfunction (40%), and dilated left atrium and ventricle (38%). Thirty-four percent of subjects had echo features consistent with dilated cardiomyopathy. Palpitation and dyspnea in combination were the only symptoms associated with severity of echo changes. There was strong negative correlation of lifetime intake amount with ejection fraction (r = -0.91, p<0.001); however its relationship with ventricular mass index was not statistically significant (r = 0.23, p>0.05). Conclusions: Prolonged non-moderate drinking causes significant echocardiographic abnormalities mainly systolic dysfunction and increased left ventricular mass index. The total lifetime and daily amount of alcohol are well correlated with systolic dysfunction; however their relationships with the left ventricular mass index were non-conclusive. Key words: Alcohol; left ventricular mass; cardiomyopathy DOI: 10.3126/jcmsn.v6i1.3598 Journal of College of Medical Sciences-Nepal, 2010, Vol. 6, No. 1, 18-28